ANALISA RADIASI PANEL SURYA TERHADAP DAYA YANG DIHASILKAN UNTUK PENERANGAN BAGIAN LUAR MESJID MIFTAHUL JANNAH DIDESA BENUA TENGAH KECAMATAN TAKISUNG - Muhammad Firman; Firda Herlina; Abdurrahman Sidiq (AL-JAZARI JOURNAL SCIENTIFIC OF MECHANICAL ENGINEERING, 2017)
The rationale for this thesis is about the application of solar power plants (SPP) in the countryside aimed specifically supplying electricity to the outside of Miftahul Jannah Mosque that housed the village hamlet of 6 sub-continental middle Takisung Pelaihari southern Kalimantan. By analyzing the authors of this study determine supply large solar cell generated power, a large catchment radiation produced by solar cell and economical aspects of connection relationship if applicable. From the results obtained from the 20 days then her whole explanation is described about average radiation and power for 20 days from 15 July to 3 August 2016 with a broad cross section of a solar panel A = 0.68 M ^ 2 is = average speed the highest radiation that is in the numbers 1017.25 W / m2 contained in the Wednesday, August 3, 2016, while the lowest was in 353.96875 W / m2 on Wednesday 20 July, 2016. while the average peak power in watts on a number 80.76285 Saturday 16 July 2016 while the lowest was in power Monday, July 25, 2016 diangka 20.3850875 watts. And radiation to the power relationship is positive and strong, while the coefficient of the determiner in can be 43.7%, which means that the rise and fall of power by the solar cell solar radiation yangdisebabkan only 43.7% and the remaining 56.3% is caused by other factors Calculation perancanagnnya total economic cost of Rp. 5.13 million. it will break even if we use solar power for 15 years is the range of Rp. 5,198,181, -.